National Identity, Citizenship and Immigration: Putting Identity in Context. (28th June 2012) - Andreouli, Eleni; Howarth, Caroline
Abstract : In this paper we suggest that there is a need to examine what is meant by "context" in Social Psychology and present an example of how to place identity in its social and institutional context. Taking the case of British naturalisation, the process whereby migrants become citizens, we show that the identity of naturalised citizens is defined by common‐sense ideas about Britishness and by immigration policies. An analysis of policy documents on "earned citizenship" and interviews with naturalised citizens shows that the distinction between "elite" and "non‐elite" migrants is evident in both the "reified" sphere of policy and the "common sense" sphere of everyday identity construction. While social representations embedded in lay experience construct ethno‐cultural similarity and difference, immigration policies engage in an institutionalised positioning process by determining migrants' rights of mobility. These spheres of knowledge and practice are not disconnected as these two levels of "managing otherness" overlap—it is the poorer, less skilled migrants, originating outside the West who epitomise difference (within a consensual sphere) and have less freedom of mobility (within a reified sphere). We show that the context of identity should be understood as simultaneously psychological and political.